ANALISA TITIK LAMPU RUANG TAMU DAN RUANG KELUARGA RUMAH TYPE 90 M2 - Ikhsan, Muhammad; Imran, Mohammad; Farid (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
This research aims to analyze the lighting needs for the living room and family room in a 90 m² house. Using a quantitative descriptive method, the findings showed that optimal lighting in the living room requires two 11-watt light points for a 7.05 m² area, while the family room needs four light points for an 11.4 m² area. Efficient lighting can be achieved through the use of LED lights, ensuring even light distribution based on the visual needs of the space. Recommendations should be validated to ensure compliance with SNI standards and visual comfort. The research provides useful guidance for the effective application of artificial lighting in 90 m² houses